Strategic management - Rothaermel, Frank T. (New York : McGraw Hill Education, 2017)
Strategic Management, 3e by Frank T. Rothaermel continues to synthesize and integrate theory, empirical research, and practical applications with current, real-world examples. This approach not only offers students a learning experience that uniquely combines rigor and relevance, but it also prepares them for the types of challenges they will face as managers in the globalized and turbulent business environment of the 21st century. Examples profile the products and services of companies that students are familiar with such as Facebook, Google, Starbucks, Apple and Uber. In its characteristic single, strong voice, Strategic Management provides students with the foundation they need to understand how companies gain and sustain competitive advantage, as well as how to become managers capable of making well-reasoned strategic decisions.
Part 1. Analysis -- What is strategy? -- Strategic leadership: managing the strategy process -- External analysis: industry structure, competitive forces, and strategic groups -- Internal analysis: resources, capabilities, and core competencies -- Competitive advantage, firm performance, and business models -- Part 2. Formulation. -- Business strategy: differentiation, cost leadership, and blue oceans -- Business strategy: innovation and entrepreneurship -- Corporate strategy: vertical integration and diversification -- Corporate strategy: strategic alliances, mergers and acquisitions -- Global strategy: competing around the world -- Part 3. Implementation. -- Organizational design: structure, culture, and control -- Corporate governance and business ethics -- Part 4. Minicases -- How to conduct a case analysis -- Part 5. Full-length cases.
Includes index.
Keywords: STRATEGIC PLANNING